Form Follows Familiarity : A Design Paradigm for Architecture in the Metaverse - Atta Idrawani, Zaini; Nadzirah, Jausus; Mohd Zariq Feeqri, Jasni; Mohamed Rashid, Embi (Springer, 2024)
The acceleration of the digitalization process during the COVID-19 pandemic has led to a mass interest in Web 3.0, blockchain and the metaverse, where digital assets traded and owned are given a new sense of authenticity. Academic discourses too seem to envision architecture in the same light, by looking into the standardization of architecture to add to its authentic position in the metaverse. We argue that it needs to be further reduced into a design paradigm, as architecture here is symbolic representations. A design dictum ‘form follows familiarity’ is proposed, as familiarity serves as the internal logic set for designing architecture in the metaverse. This study employed visual surveys on ‘Decentraland’ and ‘Voxels’ platforms on familiarity variables, which are reduced versions of buildings’ recognizability variables in the real world. We observed that architectures in the metaverse act more like an avatar and are mostly independent of architectural conscience, but the sense of familiarity has a major impact on its form as they are constantly noticeable from our surveys. This study found that the design paradigm ‘form follows familiarity’ is already practised throughout the metaverse worlds although with different degrees of negotiations, but unclear whether they are intentional. ‘Form follows familiarity’ also carries with it a philosophical agenda of understanding the fate of architecture represented in a different world that shares similar stakes of authenticity, scarcity, and ownership with the real world. We advocate more studies to continue understanding the disposition of architecture in the metaverse.